Trend inflation, wage and price rigidities, and welfare - Robert Amano; Kevin Moran; Stephen Murchison; Andrew Rennison (Bank of Canada, 2007)
This paper studies the steady-state costs of inflation in a general-equilibrium model with real per capita output growth and staggered nominal price and wage contracts. Our analysis shows that trend inflation has important effects on the economy when combined with nominal contracts and real output growth. Steady-state output and welfare losses are quantitatively important even for low values of trend inflation. Further, we show that nominal wage contracting is quantitatively more important than nominal price contracting in generating these losses. This important result does not arise from price dispersion per se but from an effect of nominal output growth on the optimal markup of monopolistically competitive labour suppliers. We also demonstrate that accounting for productivity growth is important for calculating the welfare costs of inflation. Indeed, the presence of two percent productivity growth increases the welfare costs of inflation in our benchmark specification by a factor of four relative to the nogrowth case.
Keywords: E0; E5; 330; Inflation: costs and benefits; Lohnverhandlungen; Betriebliche Preispolitik; Inflationsrate; Wirtschaftswachstum; Wohlfahrtseffekt; Theorie